Evaluation and management of gastrointestinal outflow disorders in dogs - Jinesh kumar N S (Department of Veterinary Surgery and Radiology, College of Veterinary and Animal Science, 2007)
The study was conducted in twelve animals of different breed, age and either sex suspected for gastrointestinal outflow disorders. The incidence, clinical signs, radiographic and ultrasonographic observations, haematological and serum biochemical changes, efficacy of treatment adopted, and postoperative management were studied. The incidence was more in Labrador breed of dogs. No sex predilection was observed. The age of affected animals ranged from 30 days to four years. Of foreign body obstructions, five were less than 1.5 years and was found more in females. Intussusception was observed in two male pups of less than two months of age. The most consistent clinical signs observed were vomiting and difficulty in defaecation. The affected animals were dull, weak and lethargic and two were recumbent. Two animals showed chronic intermittent vomiting. Diarrhoea was reported in cases of intussusception. Four animals had scanty black tarry faeces. Pain on palpating the abdomen was noticed in nine animals while palpable mass could be felt in three animals. Dilated intestinal loops with distension of the abdomen were the common observations. The temperature, pulse rate and capillary refill time were within normal range while respiration rate was higher. Radiography and ultrasonography was found adequate for confirmatory diagnosis in most of the cases. The different conditions included foreign body obstruction (6), gastric ulcer (1), intussusception (2), dilated colon (1), and stenosis of ileocolic sphincter (2) and were treated by enterotomy, gastrotomy, resection of ulcer, enterectomy and enteroanastamosis, colotomy and dilation of sphincter. All the animals were rehydrated before surgery and appropriate surgical treatment was carried out under general anaesthesia. Post operatively, fluid was given up to 48 hours. Liquid food followed by solid food was offered. Antibiotics and supportive medicines were continued up to seven days. The sutures were removed on eighth post operative day. Leucocytosis with neutrophilia, reduction in haemoglobin, packed cell volume, hyponatremia, hypokalemia, hypochloremia and hyperlipasemia was the major haemato biochemical changes observed. Of the twelve cases studied, nine cases recovered successfully and three animals died which included a case of gastric ulcer and two cases of intussusception.